Pediatric patient with systemic lupus erythematosus & congenital acquired immunodeficiency syndrome: An unusual case and a review of the literature - Rezaee Fariba; Chalom Elizabeth C; Mendelson Joel (BMC, 2008)
Abstract The coexistence of systemic lupus erythematosus (SLE) in patients with congenital human immunodeficiency virus (HIV) infection is rare. This is a case report of a child diagnosed with SLE at nine years of age. She initially did well on non-steroidal anti-inflammatory agents, hydroxychloroquine, and steroids. She then discontinued her anti-lupus medications and was lost to follow-up. At 13 years of age, her lupus symptoms had resolved and she presented with intermittent fevers, cachexia, myalgias, arthralgias, and respiratory symptoms. Through subsequent investigations, the patient was ultimately diagnosed with congenitally acquired immunodeficiency syndrome (AIDS).